Social Networking and the Motivations Underlying Online Purchase: Insights from the “New Normal” of the COVID-19 Pandemic Context - Cu, Le Xuan (VNU JOURNAL OF ECONOMICS AND BUSINESS, 2022)
The COVID-19 pandemic has boosted consumers to make online purchases. However, which motivations and communication channels transform online purchases in the COVID-19 context have been inadequately studied. The paper aims to unveil the importance of social networking for inducing favorable perceptions and online purchases among young consumers in the “new normal” of the pandemic. The conceptual framework is formulated due to the Uses and Gratifications Theory (UGT) and the Health Belief Model (HBM). Empirical data is collected using a web-based survey of 379 respondents who are inclined to embrace online purchases. The findings illustrate that social networking significantly influences social value, perceived utility, information quality, perceived threat, and self-efficacy. Additionally, purchase intention is motivated by antecedents such as perceived utility, information quality, social value, and perceived threat. Lastly, theoretical and managerial implications are drawn.